Continuous Monitoring of Water Quality Using Portable and Low-Cost Approaches - Tuna, Gurkan; Arkoc, Orhan; Gulez, Kayhan (SAGE PUBLICATIONS INC, 2013)
Water quality refers to the physical, chemical, and biological characteristics of water, and it is a measure of the condition of water relative to any human need or purpose. A particular problem with measuring the condition of water quality at drinking water reservoirs is the requirement of collecting a large number of samples. To handle this problem, we focus on the practical use of two different portable and low-cost approaches for continuous monitoring of water quality: miniboats loaded with sondes with probes and wireless sensor network-(WSN-) based monitoring system. These approaches bring several advantages over traditional monitoring systems in terms of cost, portability, and applicability. Our simulation studies show that these systems can be used to monitor water quality at drinking water reservoirs such as dams and holding ponds. Field tests to prove the effectiveness of the proposed systems are in progress.
Keywords: MULTIVARIATE STATISTICAL TECHNIQUES; WIRELESS SENSOR NETWORK; AIRBOAT; DESIGN; LAKE; Computer Science; Telecommunications